A Study on Strategies for University-Local Government Collaboration to Promote Lifelong Education - 한광식; 정희정; 이종원 (International Journal of Advanced Culture Technology(IJACT), 2025)
This paper analyzes the evolving role of Korean universities in lifelong education and the development of regional cooperation models amid rapid socio-economic changes such as the Fourth Industrial Revolution and demographic shifts. As labor market polarization, declining middle-skilled jobs, and population aging intensify, enhancing labor productivity and fostering regional talent through lifelong learning have become national imperatives. In response, the government has initiated policies to reposition universities as lifelong learning hubs and to strengthen partnerships with local governments and industries, as exemplified by initiatives such as the LiFE Project and the RISE system. Drawing on international case studies, recent policy trends, and an assessment of university participation in lifelong education, this study highlights the necessity of regionally tailored university lifelong education models and effective governance frameworks. It proposes differentiated models-including regional hub, industry-linked, and integrated approaches-based on local industrial structures and demographic characteristics. The findings underscore that universities must restructure their systems to support adult learners and collaborate closely with local stakeholders, while both central and local governments should provide robust policy and institutional support. Ultimately, the study suggests that such efforts will enable universities to contribute to balanced regional development and national competitiveness by establishing a sustainable, adult learner-centered lifelong education ecosystem.